The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5152/eurjrheumatol.2014.140074
|View full text |Cite
|
Sign up to set email alerts
|

Combined infliximab and methotrexate treatment improves the depressive state in rheumatoid arthritis patients more effectively than methotrexate alone

Abstract: Combined infliximab and methotrexate treatment improves the depressive state in rheumatoid arthritis patients more effectively than methotrexate alone Abstract Objective: Rheumatoid arthritis (RA) patients have a greater depressive tendency than normal subjects, and infliximab is known to provide quick therapeutic effects and to have high bioavailability for RA. We therefore investigated whether the depressive state of RA patients would be improved by infliximab.Material and Methods: The Self-Rating Depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Faecal calprotectin, conversely, indexes neutrophil infiltration into gastro-intestinal (GI) mucosal tissue and is the noninvasive gold standard for indexing inflammation of the gastrointestinal mucosa in IBD, reflecting mucosal inflammation in Crohn’s Disease (CD) more accurately than C-reactive protein or clinical scores such as the Crohn’s Disease Activity Index (CDAI) [ 19 , 20 ]. Treatment with anti-TNFα, a widely used therapy in patients with IBD[ 21 ], effectively modulates immune function in the gastrointestinal tract, and appears to reduce sickness behavior and depressive symptoms in IBD [ 22 , 23 ], rheumatoid arthritis [ 24 ] and psoriasis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Faecal calprotectin, conversely, indexes neutrophil infiltration into gastro-intestinal (GI) mucosal tissue and is the noninvasive gold standard for indexing inflammation of the gastrointestinal mucosa in IBD, reflecting mucosal inflammation in Crohn’s Disease (CD) more accurately than C-reactive protein or clinical scores such as the Crohn’s Disease Activity Index (CDAI) [ 19 , 20 ]. Treatment with anti-TNFα, a widely used therapy in patients with IBD[ 21 ], effectively modulates immune function in the gastrointestinal tract, and appears to reduce sickness behavior and depressive symptoms in IBD [ 22 , 23 ], rheumatoid arthritis [ 24 ] and psoriasis [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of data on the effect of biologic agents on depression. A study conducted in Japan found that combined infliximab and methotrexate treatment was more effective in improving the depressive state of patients with RA compared with methotrexate alone . In a Taiwan cross-sectional study, authors found a significantly lower risk of depression among patients receiving etanercept compared with the nonbiologic group .…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Japan found that combined infliximab and methotrexate treatment was more effective in improving the depressive state of patients with RA compared with methotrexate alone. 35 In a…”
Section: Jama Network Open | Psychiatrymentioning
confidence: 99%
“…The up-regulation of TNF levels in depressed patients has been demonstrated, therefore, infliximab is used to treat depression also (Rani et al, 2022 ). In 2014, a clinical study involving 34 RA-associated depression patients showed that infliximab could reduce RA disease activity and improve symptoms of depression (Miwa et al, 2014 ). However, randomized controlled trials conducted in Canada and the United States showed that infliximab did not significantly reduce depression in adults with bipolar depression compared with a placebo (McIntyre et al, 2019 ).…”
Section: What Causes Depression In Ra Patients?mentioning
confidence: 99%